Pelatihan Teknik Massage Sebagai Upaya dalam Meningkatkan Relaksasi dan Mengurangi Kelelahan Pada Ibu-Ibu Desa Karangnongko - Sestri Indah Pebrianti; Fadilah Anggraini, Shomalla; Sausan, Nabiilah Luthfi; Virian, Viani (Universitas Negeri Semarang, 2025)
Originally, humans are social creatures who have a variety of activities, whether they are ac-tivities at home or outside the home. Karangnongko Village, Karangnongko District, Klaten Re- gency itself has diverse socio-cultural conditions, what stands out in this village is that the majority are active as farmers. Because of this, the service activity created by UNNES GIAT 9 Ka- rangnongko Village is Massage Training for the women of Karangnongko Village. This massage has been around for centuries, and has become a habit carried out by our ancestors. Massage or what is known as massage is a part of natural relaxation to reduce fatigue and body aches after activities. Massage itself has many benefits, namely in the form of self-relaxation, reducing pain in the body due to activities, and maintaining body fitness, and so on. The aim of this Massage Training service is to provide more knowledge to the women of Karangnongko Village about mas- sage and improve massage skills.